[131] Experimental study of the short-circuit robustness of 600 V E-mode GaN transistors. (September 2016) - Landel, M.; Gautier, C.; Labrousse, D.; Lefebvre, S.
Abstract: This paper presents experimental robustness of 600 V GaN High Electron Mobility Transistors (HEMT) submitted to Short-Circuits (SC) operation modes. A dedicated secured test bench has been developed and designed in order to protect as quickly as possible the Device Under Test (DUT) after failure. Some devices featured a great robustness under SC and were able to support several SC of a very long duration. On the contrary, others failed immediately at the first pulse, for a low dissipated energy. The obtained results reveal a severe dispersal in terms of SC robustness for these new emerging components. Gate behavior has been also studied, showing a leakage current during each SC, destructive or not. A part of the paper is also dedicated to the study of the effects of case temperature and DC voltage on robustness. Highlights: More than 25 GaN HEMT have been submitted to destructive SC events with a specific dedicated bench. The DC voltage has been evaluated as the most significant parameter on short-circuit robustness. A statistical study demonstrated a very large disparity in the robustness of these devices under short-circuits events. All the tested devices drastically reduce by themselves the drain current during the SC event. No precursor sign of failure has been noticed just before failure, and no external degradation has been seen as far.